Road maintenance management system by public work department / Mohamad Helmi Misdi - Misdi, Mohamad Helmi (Faculty of Architecture, Planning and Surveying, 2014)
Road should be viewed as an important national assets. Like any other assets, road must be regularly maintained to keep them serviceable. The study conducted on the Road Maintenance Branch, whereby this branch was established specifically to manage the assets of the Federal Road to the Public Work Department of Malaysia. The aim o f this study is to investigate on how to improve road maintenance management system in order to reduce time and cost. The Study is carried out through interviews, questionnaires and archives from the Public Work Department. Interviews were conducted with the personnel involving in road maintenance management. The questionnaires were distributed to those who are involved in maintenance activities at the Public Work Department. The data collected were analyzed using an average index method to obtain the result. From the result, the most common problem occur during the implementation o f Road Maintenance Management System is to get the funds for the road maintenance. Public Work Department should consider monitoring the work carried out by the concessioners in order to improve the Road Maintenance Management System.